The Film Poster and Song Booklet for Zerqa (1969) - Petiwala, Ada (Film history (New York, N.Y.), 2020)
In recent years, the film poster has taken center stage in South Asian cinema studies and in the contemporary nostalgia-driven popular imagination. In analyzing Lollywood film Zerqa's (1969) song booklet and its art direction, this commentary reveals the merits of deliberating upon other mass-produced cinematic ephemera—especially publicity materials—in conjunction with or in the absence of the film text.